SUDDEN SENSORINEURAL HEARING LOSS IN THE POST-COVID-19 ERA: A SYSTEMATIC REVIEW OF ETIOLOGY, DIAGNOSIS AND MANAGEMENT - Marcin Podolak; Zuzanna Fischer; Dominika Kolenda; Natalia Ramlau; Michalina Cyrulik; Marta Prager-Zimny; Beata Imbirska; Michalina Janiszewska; Michalina Simachi; Michał Hładki (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Sudden sensorineural hearing loss (SSHL) is a rare otorhinolaryngological emergency that, if not identified early, may lead to permanent hearing impairment. It is characterized by a sudden unilateral hearing loss developing within 72 hours, with a ≥30 dB reduction across three contiguous frequencies on pure-tone audiometry. Its pathophysiology remains poorly understood, and in over 70% of cases, the cause is idiopathic. SSHL is often unaccompanied by systemic symptoms but may present as a sensation of a “blocked ear,” which contributes to diagnostic delays. The estimated incidence ranges from 5 to 27 per 100,000 individuals annually, with a noted increase in cases during and after the COVID-19 pandemic.Aim of the study: To summarize current knowledge on the etiology, diagnosis, and management of SSHL, and to review studies examining its potential link to SARS-CoV-2 infection.Materials and methods: Data were collected from PubMed, Mendeley, and the Clinical Practice Guideline on Sudden Hearing Loss (Otolaryngology–Head and Neck Surgery journal). Searches used terms such as “Sudden Sensorineural Hearing Loss,” “Idiopathic Hearing Loss,” and “SSHL and COVID-19.”Conclusion: SSHL poses a diagnostic and therapeutic challenge due to its rarity and narrow therapeutic window. Glucocorticoids—administered orally or via intratympanic injection—remain the primary treatment. Diagnostic work-up should rely on clinical evaluation and avoid unnecessary tests, such as CT or routine labs, unless specifically indicated. Poorer prognosis is associated with vertigo, dizziness, advanced age, and comorbidities. An increase in SSHL cases post-COVID-19 highlights the need for further research into pathogenesis, prognostic factors, and individualized therapy.